Chronic foot ulcers - Rule out cutaneous tuberculosis! - Sunita Arora; Tejinder Kaur; Guneet Gandhi (Wolters Kluwer Medknow Publications, 2021)
Cutaneous tuberculosis is a form of extrapulmonary tuberculosis and is seen in a small but significant subset of patients seeking dermatology outpatient services. Children constitute a significant proportion of overall cases of cutaneous tuberculosis. We report the case of an 8-year-old boy who presented with multiple discharging ulcers over bilateral feet. High suspicion of cutaneous tuberculosis led to early diagnosis and initiation of therapy. Cutaneous tuberculosis can have a varied clinical presentation. We wish to draw attention to mycetoma-like presentation of cutaneous tuberculosis characterized by chronic discharging foot ulcers.